Peran Guru PPKn dalam Mengembangkan Nilai-Nilai Wawasan Kebangsaan dan Rasa Cinta Tanah Air - Rani Asmara Hanipasa; Rohmad Widodo; Nurul Zuriah (Jurnal Civic Hukum, 2017)
Nationality insight and love to the country shows an individual in understandinghis Nations and country. Target of this research is: (1) to know and describe Pancasila and Citizenship teacher’s role in developing nationality insight and love to the country by is state SMP 3 Malang, (2) to konow and describe of supporter factors and inhibiting factors in developing nationality insight dan love to the country by is state SMP 3 Malang, (3) to know and describe solution what can be gone through to overcome constraint factors in developing nationality insight and love to the country in state SMP 3 Malang. Based on that research hence researcher done observation in state SMP 3 Malang. Interview with principal, teacher of PPKn, and student of state SMP 3 Malang that furthermore so called as informant, and alco conduct documentation.The research concludes that: (1) Teacher’s role in developing nationality insight and love to the countryto students is by giving examples and direction and motivation (2) all supporting factors comes from all teachers, parents, students and school facility is truly supported. Inhibiting factors come from the students themselves. Their age less mature, old teachers commonly make assessment only from cognitive aspect (3) Solution is by supporting Students Organization (OSIS), all teachers keep learning andexploring curriculum further.